State’s response to cases of child sexual abuse in Alto Paraná: Analysis of cases in Iguazú, Juan León Mallorquín and Juan E. O’Leary from 2017 and 2021 (Legal journal - Research in Legal and Social Sciences, 2021)
This article relates to child sexual abuse cases that were filed at the Public Ministry in Alto Paraná. This type of crime is gradually increasing, considering that in rural regions this offense often is not reported. For that matter, the methodology used is of a mixed approach, of descriptive level. The samples were the criminal investigation’s booklets of Unit 1 and 2 of Caaguazu’s Zonal Public Prosecution Service. The technique was the viewing and analysis of documents which showed the increase of this type of crime. With the obtained results it is possible to establish numerically the observed population by taking the following variables: documented cases from 2017 and 2021 at Public Prosecution Service’s offices in Yguazu, national cases and their departmental distribution, cases before and during the pandemic, which also showed a slight decrease of these cases during the pandemic in 2020. The study also includes information on the bonds between the persons charged and the victims, preference regarding gender, institutions involved in reporting the crime, and the organisms and institutions with obligation to report. Furthermore, the evidence elements are verified, in order display them in hearings, considering the particularities of this type of crime, and finally this paper introduces statistics of convictions, concluded investigations and dismissed cases for comparison.
Keywords: sexual abuse; children; adolescents; pedophilia